The Value of Metacognitive Control Training in Enhancing Moroccan EFL Learners’ Reading Process in Tertiary Education - Msaddek, Mohammed (International Journal of English Language Education, 2021)
The present study, drawing on a quasi-experimental design, is geared towards probing into the value of the delivery of metacognitive control training in improving English as a foreign language (EFL) learners’ performance in textual reading at the university level. To investigate this issue at length, two EFL first-semester groups majoring in English studies were selected as the main respondents. The treatment group trained in metacognitive control consists of sixty-three (n=63) students and the non-treatment group receiving no training is comprised of fifty (n=50) students. These two groups were presented with both a narrative and an expository reading text at the pre- and post-intervention phase along the continuum of the semester (Semester One) and were administered a ‘self-report questionnaire’ at each phase. The findings feature that the treatment group reflected a more significant measure of improvement in terms of the executive and metacognitive control exercised during the reading process than the non-treatment group did. Thus, the study puts forward the implied view that metacognitive control instruction with regard to reading comprehension is to be embedded in the university curriculum for the optimization of the learners’ reading process.